ANALISIS PELAKSANAAN PROGRAM KESETARAAN GENDER DIBADAN KESATUAN BANGSA DAN POLITIK PROVINSI DKI JAKARTA TAHUN 2019 - Faizah Julina (PANDITA : Interdisciplinary Journal of Public Affairs, 2021)
The demand for equal roles between men and women gives rise to the concept of gender equality due to the rampant sexist reactions and rejection of feminine thinking from some men who have long been comfortable with social conditions that prioritize their position in several governmental institutions or agencies. This can be seen in city government, parliament, and other government offices most of which are still occupied by men rather than women. This research is a qualitative descriptive study. Data collection was carried out through in-depth interviews with relevant and reliable informants. This research was conducted to analyze the implementation of the gender equality program in the National and Political Unity Agency of DKI Jakarta Province in 2019 using the Orinton Purba theory. This theory states that there are four factors that influence gender equality analysis, namely access, control, participation and benefits. From this research, it was found that there is an obstacle in the implementation of gender equality program, namely the lack of government attention. Some of the efforts made by the National and Political Unity Agency of DKI Jakarta Province to overcome this obstacle are providing direction and information as political science knowledge for women so that they can participate and become part of government organizations and political parties so that they are able to occupy legislative seats and meet the 30% quota for women.